2021
DOI: 10.24237/djes.2021.14304
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses the causes of cost deviation in Iraqi construction projects

Abstract: Root cause analysis techniques are an excellent choice for identifying the root causes of cost deviation in Iraqi construction projects. Many root cause analysis tools, such as the Fishbone diagram (FD), Pareto diagram (PD), and 5-Why analysis, have started to emerge from the literature as standard guidelines for identifying root causes. This study identified eighteen causes of cost deviation in construction projects, which they classified into three major groups (planning causes, designing causes, and executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is in the interest of the stakeholders involved to complete the project according to the required quality. However, due to poor management, supervision and control, success becomes difficult [1]. In Iraq, the construction industry suffers many obstacles and difficulties that lead to cost deviations and inability to achieve project objectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in the interest of the stakeholders involved to complete the project according to the required quality. However, due to poor management, supervision and control, success becomes difficult [1]. In Iraq, the construction industry suffers many obstacles and difficulties that lead to cost deviations and inability to achieve project objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [3] found that common factors for cost deviations were design failures, material price differences, inadequate project planning, project scope changes, and design changes. Authors in [1] concluded that cost deviation is caused by insufficient information, poor planning, unclear employer requirements, and change in orders during the implementation phase. Authors in [4] mentioned that the use of modern technologies and tools, the use of modern design programs, the establishment of solid rules, and the use of work-study techniques are factors that contracting companies should focus on.…”
Section: Introductionmentioning
confidence: 99%
“…A construction project will be successful if its technical goals are aligned with its budget and the budget is not exceeded. It is difficult to envisage a construction project being completed without cost variances and schedule delays, which may occur at any time during the procedure due to various factors such as poor management, supervision, and control [1]. Most construction projects require the completion of a specific set of operations to deliver a specific product.…”
Section: Introductionmentioning
confidence: 99%